The determinants of FDI sectoral structure in the Central and East European EU countries - Mario Pečarić; Tino Kusanović; Pavle Jakovac (Economies, 2021)
The EU model of market integration, based on financial openness, leads to divergence and sectoral specialization, which makes the convergence of Central and East European EU countries (CEE) in the EU questionable. The idea of the paper is that forms of foreign direct investment (FDI) have a differential effect on the growth and development of countries-i.e., it is assumed that FDI inflows into the manufacturing sector have a greater intensity and impact on economic growth than inflows into the services sector. Therefore, the aim of this paper is to analyze the system determinants and transmission mechanisms of the sectoral structure of FDI inflows on the sample of 10 CEE for the period 1995-2019. Following a critical analysis of previous research, a panel model was constructed in the empirical section. A developed credit market and the purchasing power of residents lead to greater capital inflows into the services sector, while a higher GDP growth rate and a depreciated real exchange rate lead to higher inflows into the manufacturing sector. The conclusion of the paper is that changing the structure of the domestic economy based on clear industrial and investment policies is the best way to attract developmentally efficient FDI.
Keywords: 330; economic growth; CEE countries; real exchange rate; sectoral structure of FDI inflows